2005
DOI: 10.1128/aem.71.3.1453-1461.2005
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Noroviruses and Other Enteric Viruses in Sewage and Surface Waters in The Netherlands

Abstract: Since virus concentrations in drinking waters are generally below the detection limit, the infectious risk from drinking water consumption requires assessment from the virus concentrations in source waters and removal efficiency of treatment processes. In this study, we estimated from reverse transcription-PCR on 10-fold serially diluted RNA that noroviruses, the most prevalent waterborne gastroenteritis agents, were present at 4 (0.2 to 38) to 4,900 (303 to 4.6 ؋ 10 4 ) PCR-detectable units (PDU) per liter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
205
1
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(223 citation statements)
references
References 55 publications
10
205
1
7
Order By: Relevance
“…The ratios of culturable viruses to somatic coliphages (mainly with reference to enteroviruses detected by cell culture) are 10:10 4 or 10:10 5 in the scenarios for which data on both are available. The claim is true for raw sewage, secondary and tertiary effluents [72][73][74][75][76][77], surface waters [73,[78][79][80], and sludge [81,82]. The same ratio is true for infectious rotaviruses detected by cell culture followed by qRT-PCR [83].…”
Section: Concentration Methodsmentioning
confidence: 80%
“…The ratios of culturable viruses to somatic coliphages (mainly with reference to enteroviruses detected by cell culture) are 10:10 4 or 10:10 5 in the scenarios for which data on both are available. The claim is true for raw sewage, secondary and tertiary effluents [72][73][74][75][76][77], surface waters [73,[78][79][80], and sludge [81,82]. The same ratio is true for infectious rotaviruses detected by cell culture followed by qRT-PCR [83].…”
Section: Concentration Methodsmentioning
confidence: 80%
“…Tajima et al (2007) reported that norovirus was detected in 20 of 22 specimens (91%) in the secondary effluent and 20 of 28 specimens (71%) in the reclaimed water after tertiary treatments. In a study from the Netherlands (Lodder & de Roda Husman 2005), the concentration of norovirus in sewage was higher than that of rotavirus. The difference might be attributed to the epidemiological situation, the method used to concentrate the viruses, or even to the primer sets used for detection.…”
Section: Discussionmentioning
confidence: 99%
“…The presence and diversity of NoVs in surface water has been described in Asia [12,13], Europe [14] and South America [15,16]. However, no investigations have addressed the occurrence and molecular epidemiology of NoVs in surface water, or other water sources, in SA.…”
Section: Introductionmentioning
confidence: 99%